76 Patients (PTS) with recurrent gynecologic cancer whose tumors have activating wnt pathway mutations respond better to DKN-01, a DICKKOPF-1 (DKK1) inhibitor. (18th September 2019) - Arend, R; Castro, C; Matulonis, U; Hamilton, E; Gunderson, C; LyBarger, K; Goodman, H; Duska, L; Mahdi, H; ElNaggar, A; Kagey, M; Barroilhet, L; et al.
Abstract : Objectives: Wnt/β-catenin signaling is frequently dysregulated in gynecologic malignancies. CTNNB1, APC and RNF43 mutations cause pathway activation; CTNNB1 stabilizing mutations lead to elevated DKK1 expression which promotes an immune suppressive tumor microenvironment. Neutralization by DKN-01 (D), a mAb against DKK1, is being tested in a phase 2 basket study. Methods: Eligibility included recurrent endometrial cancer (EC) or platinum resistant/refractory ovarian cancer (OC) enriched (∼50%) for Wnt signaling-related genetic alterations. Subgroup analysis was done in pts with genetic alterations associated with activation of Wnt/β-catenin signaling ( CTNNB1, APC or RNF43 ). Pts were assigned (MD discretion) to receive D (300 mg on Days 1 & 15) or D + paclitaxel (P) (80 mg/m2 on Days 1, 8 and 15) of a 28-day cycle. Primary endpoint is ORR; exploratory endpoints: DKK1 expression (serum/plasma/tumor), tumor genetics, infiltrating immune cells, and β-catenin IHC. Results: 80 pts are enrolled: D (n=33, 19 EC, 14 OC); D + P (n=47; 28 EC, 19 OC); 18 pts with CTNNB1 (n=13), APC (n=2), RNF43 (n=2), or CTNNB1 + RNF43 (n=1). 54 pts evaluable for response (table 1 ). D and D + P were safe and well tolerated with no additive toxicities. The trial is ongoing; updated safety, efficacy and correlative work are pending. Conclusions: D and D + P have activity in pts with recurrent gyn cancers; the role of Wnt/β-catenin pathway activation as a potential biomarker for response is currently under study. Clinical trial information: NCT03395080 .